Chickpea seed endophyte Enterobacter sp. mediated yield and nutritional enrichment of chickpea for improving human and livestock health - Mukherjee, Arpan; Gaurav, Anand Kumar; Chouhan, Gowardhan Kumar; Singh, Saurabh; Sarkar, Ankita; Abeysinghe, Saman; Verma, Jay Prakash (Frontiers in Nutrition, 2024)
Chickpeas (Cicer arietinum L.) are used as a good source of proteins and energy in the diets of various organisms including humans and animals. Chickpea straws can serve as an alternative option for forage for different ruminants. This research mainly focussed on screening the effects of adding beneficial chickpea seed endophytes on increasing the nutritional properties of the different edible parts of chickpea plants. Two efficient chickpea seed endophytes (Enterobacter sp. strain BHUJPCS-2 and BHUJPCS-8) were selected and applied to the chickpea seeds before sowing in the experiment conducted on clay pots. Chickpea seeds treated with both endophytes showed improved plant growth and biomass accumulation. Notably, improvements in the uptake of mineral nutrients were found in the foliage, pericarp, and seed of the chickpea plants. Additionally, nutritional properties such as total phenolics (0.47, 0.25, and 0.55 folds), total protein (0.04, 0.21, and 0.18 folds), carbohydrate content (0.31, 0.32, and 0.31 folds), and total flavonoid content (0.45, 027, and 0.8 folds) were increased in different parts (foliage, pericarp, and seed) of the chickpea plants compared to the control plants. The seed endophyte-treated plants showed a significant increase in mineral accumulation and improvement in nutrition in the different edible parts of chickpea plants. The results showed that the seed endophyte-mediated increase in dietary and nutrient value of the different parts (pericarp, foliage, and seeds) of chickpea are consumed by humans, whereas the other parts (pericarp and foliage) are used as alternative options for forage and chaff in livestock diets and may have direct effects on their nutritional conditions.